Developing Inner Speech for Arabic Fluency: Evidence from the Islamic Education Institution in Malaysia - Masnun Masnun; Nur Hanifansyah; Menik Mahmudah; Nur Aina Faqihah (Universitas Islam Negeri Jurai Siwo Lampung, 2026)
Background: Arabic-speaking fluency remains a central yet challenging goal in Malaysian Islamic education, where Arabic functions as both a religious and academic language. Although students receive formal instruction in grammar, vocabulary, and reading, many still rely on mental translation before speaking, limiting spontaneity and confidence. Inner speech, which is understood as silent Arabic self-talk, subvocal rehearsal, and internal sentence formulation, offers a cognitive pathway for strengthening oral fluency. Research Objectives: This study examines the extent to which students in Islamic educational institutions in Malaysia develop inner speech in Arabic and investigates how it contributes to speaking fluency, confidence, and self-regulation. Methodology: A mixed-methods design involving 60 final-year secondary and diploma-level students from two Islamic education institutions in Kedah, Malaysia, was employed. Data were collected through questionnaires, semi-structured interviews with 15 participants, classroom observations, and institutional documents. Quantitative data were analyzed using descriptive statistics, chi-square testing, Pearson correlation, and partial correlation, whereas qualitative data were examined through thematic analysis and triangulation. Results: The findings show that 68.3% of students regularly used Arabic inner speech. Advanced learners demonstrated stronger direct Arabic formulation, whereas beginners remained dependent on Malay-to-Arabic mental translation. A significant relationship was found between the proficiency level and the inner speech pattern, χ²(2)=15.34, p<0.001, Cramer’s V=0.51. Arabic inner speech was also moderately correlated with perceived speaking fluency, r=0.58, p<0.001. Unique Contribution: This study extends inner speech theory to Arabic language acquisition in Islamic educational contexts and introduces inner Arabic thought as a measurable psycholinguistic factor in fluency development. Conclusion: By supporting rehearsal, vocabulary retrieval, self-correction, confidence building, and emotional regulation, inner speech functions as a cognitive bridge between linguistic knowledge and spontaneous Arabic speaking. Recommendations: Digital-based inner speech training through AI voice assistants, speech-recognition tools, or mobile Arabic self-talk diaries should be explored in future studies to strengthen internal rehearsal, reduce mental translation, and improve spontaneous Arabic fluency.